Lateral constrained wrinkling of the film with partial contact. (1st March 2022) - Liu, Mengxiong; Xue, Zhiming; Wang, Yafei; Li, Xide; Wang, Changguo
Highlights: A coupled interfacial sliding and lateral constraints model of film wrinkling is established. The film deformation goes through the process from compressing to wrinkling to point contact to line contact to model transition. Increasing the interfacial strength and stiffness accelerates the film wrinkling. Increasing the interfacial strength and stiffness increases the interface failure threshold. Shear-lag effect contributes to the size effect of the graphene wrinkling. Abstract: This paper establishes three analytical models, including the interface bonded type (B-type), interface sliding type (S-type) and the lateral constrained type (C-type), to reveal the effects of the partial contact and lateral constraints on the film wrinkling behaviors. Due to the geometrical and contact nonlinearities, a numerical method is applied to solving the displacement and stress fields, and the shear-lag effect caused by contact is included. The deformation of the film can be characterized by 5 processes, firstly compressing (I), secondly wrinkling (II), then the growing of wrinkled part giving rise to point contact (III), line contact (IV), and finally mode transition(V), which are verified by a demonstrative experiment. Moreover, effects of the contact parameters, including the interfacial strength, interfacial stiffness and the initial contact region length, on the deformation of the film are analyzed. Finally, the established models are applied to characterize the wrinkling behaviors of a graphene contacting to the polyethylene terephthalate (PET). The minimum pre-existing defect size for graphene wrinkling is 7 nm, less than which the interface failure precedes the film wrinkling. The critical wrinkling strain shows significant size effect when the graphene length is less than 13μm, where all the interfaces participate the load transfer. The obtained results are consistent with the experimental and the numerical data given in the references, where the differences are also discussed detailly. Graphical abstract: Image, graphical abstract